Variant histology, IgD and CD30 expression in low‐risk pediatric nodular lymphocyte predominant Hodgkin lymphoma: A report from the Children's Oncology Group. Issue 1 (12th August 2017) - Untanu, Ramona Vesna; Back, Jason; Appel, Burton; Pei, Qinglin; Chen, Lu; Buxton, Allen; Hodgson, David C.; Ehrlich, Peter F.; Constine, Louis S.; Schwartz, Cindy L.; Hutchison, Robert E.
Abstract: Background: Histologic prognostic factors have been described for nodular lymphocyte predominant Hodgkin lymphoma (NLPHL). This study examines histologic and immunophenotypic variants in a clinical trial for pediatric NLPHL. Procedure: One hundred sixty‐eight cases of localized NLPHL were examined for histologic variants, CD30 and immunoglobulin D (IgD) expression, and outcome. Histologic types were scored categorically as 0 = 0, 1 ≤ 25%, and 2 > 25% of the sample. Results: Fifty‐eight (35.1%) cases showed only typical nodular with or without serpiginous histology (types A and B). The remainder showed mixtures of histologies. The numbers of patients with score 2 are 85 (50.6%) type A, 21 (12.5%) type B, 46 (27.4%) with extranodular large B cells (type C), 3 with T‐cell‐rich nodular pattern (type D), 55 (32.7%) with diffuse T‐cell‐rich (type E) pattern, and 2 (1.2%) with diffuse B‐cell pattern (type F). Higher level of types C ( P = 0.048) and D ( P = 0.033) resulted in lower event‐free survival (EFS). Cytoplasmic IgD was found in 65 of 130 tested (50%), did not significantly associate with EFS but positively correlated with types C and E histology ( P < 0.0001) and negatively correlated with types A ( P = 0.0003) and B ( P = 0.006). Seventeen (10%) expressed CD30, with no adverse effect. Conclusions: Variant histology is common in pediatric NLPHL, especially types C and E, which are associated with IgD expression. Type C variant histology and possibly type D are associated with decreased EFS, but neither IgD nor CD30 are adverse features. Variant histology may warrant increased surveillance, but did not affect overall survival.